A coating current collector and preparation method thereof and aqueous battery
By setting up coating collector with glue coating on the polar audio surface of the water -based battery, the problem of electrolyte precipitated in the electrolyte in the electrolytes is solved, and the tensile strength of the collector is improved and the battery cycle life is extended.
Patent Information
- Application Number
- CN202411328089.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-24
AI Technical Summary
After the water-based battery is charged and discharged for a long time, the electrolyte precipitates in the electrolyte at the pole ear of the current collector, resulting in corrosion of the current collector, reduced battery capacity and attenuation of the cycle life.
A coating set is provided with glue coating on the surface of the polar ear. The preparation raw materials of the adhesive coating include water, organic solvent, coating glue, dispersion, and anti -retractors. Add a coating set with high tensile strength and good insulators through vacuum decontamination treatment and appropriate amount of dispersant and anti -shrinking agent.
Effectively block direct contact with the streaming, inhibit the corrosion of the collector, extend the cycle life of the water system battery, and improve the overall electrochemical performance of the battery.
Smart Images

Figure CN118867608B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aqueous batteries, and in particular to a coating current collector, a preparation method thereof, and an aqueous battery. Background Art
[0002] Aqueous batteries are safer than organic batteries because the electrolyte solvent used in aqueous batteries is water, which makes the ionic conductivity of aqueous batteries high. They are also highly safe and environmentally friendly when used in the energy storage industry.
[0003] In practical applications, after a long period of cyclic charge and discharge, the electrolyte in the electrolyte will precipitate at the ear of the current collector, which can easily cause corrosion of the current collector, increase of the ohmic polarization of the pole piece, reduction of battery capacity, and reduction of cycle life. Therefore, how to avoid such phenomena and improve the overall electrochemical performance of aqueous batteries has become an urgent problem to be solved. Summary of the invention
[0004] In view of the above situation, the present invention aims to provide a coated current collector and a preparation method thereof and an aqueous battery, which can at least solve one of the following technical problems: the electrolyte in the electrolyte will precipitate at the pole ear of the current collector of the existing aqueous battery, causing corrosion of the current collector, reduced battery capacity, and attenuated cycle life.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] On the one hand, the present invention provides a coated current collector, which includes a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is provided on the surface of the pole ear. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent; the mass of the dispersant is 2%~10% of the mass of the coating glue, and the mass of the anti-shrinkage agent is 0.05%~2% of the mass of the coating glue.
[0007] Furthermore, the rubber coating is provided on 30% to 80% of the surface of the lower end of the tab.
[0008] Furthermore, the adhesive coating is obtained by coating with an adhesive liquid, wherein the coating adhesive is added into a mixed solution of water and an organic solvent, and then a dispersant and an anti-shrinkage agent are added in sequence to obtain the adhesive liquid.
[0009] The present invention also provides a method for preparing the above-mentioned coating current collector, comprising the following steps:
[0010] Step 1, mixing water and an organic solvent to obtain solution A;
[0011] Step 2, adding the coating glue to solution A and mixing to obtain solution B;
[0012] Step 3, adding the dispersant and the anti-shrinkage agent to the solution B in sequence and mixing them to obtain a solution C;
[0013] Step 4, subjecting solution C to vacuum degassing treatment;
[0014] Step 5: coating solution C on the lower end surface of the electrode ear of the current collector; and then drying to obtain a coated current collector.
[0015] Furthermore, in step 2, the volume ratio of the mass of the coating glue to the solution A is 1 g: 1-10 mL.
[0016] Furthermore, in step 3, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating rubber.
[0017] Furthermore, in step 3, the mass of the anti-shrinkage agent is controlled to be 0.05% to 2% of the mass of the coating adhesive.
[0018] Furthermore, in step 1, the stirring speed is 50-300 r / min.
[0019] Furthermore, in step 5, the drying temperature is 60-200°C.
[0020] The present invention also provides an aqueous battery, which comprises the above-mentioned coating current collector.
[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0022] a) The coated current collector of the present invention has a rubber coating on its tabs. The rubber coating has insulating properties and can block direct contact between the electrolyte and the current collector inside the coating, thereby preventing the conductive particles in the electrolyte from exchanging electrons with the current collector, thereby inhibiting corrosion of the current collector. The coated current collector has a rubber coating on its tabs, and the conduction of electrons occurs inside the current collector, which will not increase the ohmic resistance of the current collector part in the battery, and has no inhibitory effect on the cycle performance of the battery.
[0023] b) In the preparation method of the coated current collector of the present invention, the glue solution is subjected to vacuum degassing treatment to prevent air from being mixed into the glue solution during the preparation process, and to prevent air from causing incomplete subsequent drying and film formation of the glue solution when the glue solution is coated on the electrode ears of the current collector, and the current collector is exposed and corroded by salt creep.
[0024] c) In the preparation method of the coated current collector of the present invention, by adding an appropriate amount of dispersant, the glue liquid can be effectively and evenly dispersed, and a uniformly thick and dense coating can be prepared when preparing the coated current collector, and it can be firmly attached to the surface of the collector's pole ear, effectively enhancing the tensile strength of the collector's pole ear, making it less likely to break; by adding a trace amount of anti-shrinkage agent, the glue liquid can be effectively prevented from excessively shrinking during the pre-drying and drying process of the current collector, causing deformation and damage to the current collector.
[0025] d) The current collector prepared by the present invention is a new type of coated current collector with conductive middle layer and insulating outer layer. Compared with the traditional current collector, it has higher tensile strength and can effectively inhibit the salt creep phenomenon of the electrolyte, alleviate the corrosion of the current collector, and extend the cycle life of the aqueous battery; for example, the tensile strength of the tab of the coated current collector of the present invention can reach more than 6.5N, which is more than 1.3 times the tensile strength of the traditional current collector without glue coating. The coated current collector of the present invention is suitable for aqueous batteries with electrolytes of different components and has strong adaptability.
[0026] e) The aqueous battery of the present invention has a long cycle life. For example, the cycle life of the aqueous battery of the present invention reaches more than 200 cycles, which is more than twice that of a conventional battery without a gel-coated current collector.
[0027] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components;
[0029] Figure 1 is a macroscopic photograph of the coated current collector;
[0030] Figure 2 is a comparison diagram of the current collectors of Example 1 of the present invention and Comparative Example 1;
[0031] Figure 3 is a comparison diagram of the tensile strength of the current collector tabs of Example 1 of the present invention and Comparative Example 1;
[0032] Figure 4 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 1 of the present invention and Comparative Example 1;
[0033] Figure 5 1 is a cycle performance diagram of an aqueous sodium ion battery assembled in Example 1 of the present invention and Comparative Example 1;
[0034] Figure 6 is a comparison diagram of the current collectors of Example 2 of the present invention and Comparative Example 2;
[0035] Figure 7 This is a comparison chart of the tensile strength of the current collector tabs of Example 2 of the present invention and Comparative Example 2;
[0036] Figure 8This is a comparison diagram of the salt creep of the current collector after battery cycling between Example 2 of the present invention and Comparative Example 2;
[0037] Fig. 9 It is a cycle performance diagram of the aqueous zinc ion battery assembled by Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0038] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0039] The present invention provides a coating current collector, such as Figure 1 As shown, the coated current collector includes a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is provided on the surface of the pole ear. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.
[0040] Specifically, the adhesive coating is arranged on 30% to 80% of the lower surface of the tab, that is, the adhesive coating is arranged along the end of the tab connected to the current collector matrix in a direction away from the current collector matrix, and the area of the adhesive coating accounts for 30% to 80% of the area of the tab.
[0041] Specifically, in order to prevent contamination by impurities, deionized water may be used.
[0042] Specifically, the organic solvent may be N-methyl-2-pyrrolidone (NMP), N , N - one or more of dimethylformamide (DMF), triol, n-hexane, tetrahydrofuran (THF), hydroxypyridine and acetonitrile. For example, the organic solvent may be DMF and hydroxypyridine, and the volume ratio of DMF to hydroxypyridine is 0.8-1.5:1.
[0043] Specifically, the coating adhesive can be one or more of ABS plastic adhesive, polyacrylic resin, epoxy resin, polyvinyl chloride, organic silicone adhesive, polyvinyl acetate emulsion and VAE emulsion. For example, the coating adhesive can be epoxy resin and VAE emulsion, and the mass ratio of epoxy resin to VAE emulsion is 1.5-2.5:3.
[0044] Specifically, the dispersant may be one or more of water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphate, sodium lauryl sulfate, methylpentyl alcohol, polyacrylamide, fatty acid polyethylene glycol esters, and cellulose derivatives. For example, the dispersant may be water glass and sodium pyrophosphate, and the mass ratio of water glass to sodium pyrophosphate is 0.8-1.5:2.
[0045] Specifically, the anti-shrinkage agent may be one or more of polypropylene oxide, inorganic vehicle ethylene glycol and monoglyceride.
[0046] Specifically, the role of water is to prevent the solvent from evaporating too quickly during the drying process, causing some adhesive coatings to shrink. Excessive use of water will result in low solute concentration, increased fluidity, and uneven film formation; too little water will result in low solvent content, too fast solvent evaporation rate, and greater stress when the coating is dried. Therefore, the volume ratio of water to organic solvent is controlled to be (0.01~1):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, preferably (0.1~0.5):1.
[0047] Specifically, too much coating glue can easily lead to a solution that is too viscous, difficult to apply, and prone to produce large stress when drying. Too little coating glue can lead to a thinner solution that is also difficult to apply, takes a long time to dry, and has a poor film-forming effect.
[0048] Specifically, considering that too much dispersant can easily cause the glue coating to be loose, causing small solvent molecules in the electrolyte to enter the glue layer and directly contact the current collector, thereby corroding the current collector. Too little dispersant cannot achieve a good dispersion effect, resulting in uneven film formation of the coating. Therefore, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating glue, such as 3%, 5%, 7%, 9%; preferably 3% to 7%.
[0049] Specifically, considering that too much anti-shrinkage agent will easily release the internal stress of the adhesive layer, causing the bond energy between the adhesive layer molecules to become weak, and it is difficult to form a dense coating; too little anti-shrinkage agent will cause excessive stress in the adhesive layer and serious inward shrinkage of the tab. Therefore, the weight of the anti-shrinkage agent is controlled to be 0.05% to 2% of the coating adhesive weight, such as 0.1%, 0.12%, 0.15%, 0.17%, 0.19%; preferably 0.1% to 1%.
[0050] Specifically, the adhesive coating has good insulation, compactness, and corrosion resistance, and can block direct contact between the electrolyte and the current collector inside the coating, avoiding electron exchange between the conductive particles in the electrolyte and the current collector, thereby inhibiting corrosion of the current collector.
[0051] Specifically, the adhesive coating is obtained by coating with an adhesive liquid, wherein the coating adhesive is added into a mixed solution of water and an organic solvent, and then a dispersant and an anti-shrinkage agent are added in sequence to obtain the adhesive liquid.
[0052] Specifically, the thickness of the adhesive coating is 5-200 μm, preferably 10-100 μm.
[0053] The present invention also provides a method for preparing a coating current collector, comprising the following steps:
[0054] Step 1, mixing water and an organic solvent to obtain solution A;
[0055] Step 2, adding the coating glue to solution A and mixing to obtain solution B;
[0056] Step 3, adding the dispersant and the anti-shrinkage agent to the solution B in sequence and mixing them to obtain a solution C;
[0057] Step 4, subjecting solution C to vacuum degassing treatment;
[0058] Step 5: coating solution C on the lower end surface of the electrode ear of the current collector; and then drying to obtain a coated current collector.
[0059] Specifically, in the above step 1, the role of water is to prevent the subsequent current collector from evaporating too quickly during the drying process, causing some glue coatings to shrink, resulting in deformation and damage to the current collector. Excessive use of water will lead to a low solute concentration in solution C, increased fluidity, and uneven film formation on the surface of the current collector; too little water will cause a low solvent content in solution C, a too fast solvent evaporation rate, and a large stress when the coating of the current collector is dried, causing the pole ear to deform and shrink. Therefore, the volume ratio of water to organic solvent is controlled to be (0.01~1):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, preferably (0.1~0.5):1.
[0060] Specifically, in the above step 1, too high a stirring speed can easily cause the solution to splash, causing the solution concentration to change, and too low a stirring speed can make it difficult to disperse the solute, resulting in insufficient solute dissolution or too long a stirring time, and low production efficiency. Therefore, the stirring speed is controlled to be 50-300 r / min, such as 80 r / min, 100 r / min, 130 r / min, 150 r / min, 180 r / min, 200 r / min, 230 r / min, 250 r / min, 280 r / min; preferably 100-260 r / min.
[0061] Specifically, in the above step 2, too much mass of the coating glue will easily cause the solution to be too viscous, making it difficult to coat, and it is easy to generate large stress during drying, causing deformation of the collector ear. Too little mass of the coating glue will result in a thinner solution, which is also difficult to coat. The solution takes a long time to dry and the film-forming effect is poor. Therefore, the volume ratio of the mass of the coating glue to solution A is controlled to be 1g: (1~10)mL, for example, 1g: 2mL, 1g: 5mL, 1g: 7mL, 1g: 9mL; preferably 1 g: (2~8)mL. It should be noted that the volume ratio of the mass of the coating glue to solution A here only represents the proportional relationship between the two. During the production process, the amount of the two can be determined according to actual needs.
[0062] Specifically, in the above step 3, considering that too much mass of the dispersant may cause the glue layer to be loose, small solvent molecules in the electrolyte may enter the glue layer and directly contact the current collector, thereby corroding the current collector. Too little mass of the dispersant cannot achieve a good dispersion effect, resulting in uneven film formation of the coating. Therefore, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating glue, such as 3%, 5%, 7%, 9%; preferably 3% to 7%.
[0063] Specifically, in the above step 3, it is considered that too much anti-shrinkage agent will easily release the internal stress of the adhesive layer, causing the bond energy between the adhesive layer molecules to become weak, making it difficult to form a dense coating; too little anti-shrinkage agent will cause excessive stress in the adhesive layer and serious inward shrinkage of the tab. Therefore, the mass of the anti-shrinkage agent is controlled to be 0.05% to 2% of the mass of the coating adhesive, such as 0.1%, 0.12%, 0.15%, 0.17%, 0.19%; preferably 0.1% to 1%.
[0064] Specifically, in the above step 4, considering that the vacuum degree is too large, the boiling point of the solution is too low, and the solution will boil violently during degassing; if the vacuum degree is too small, the tiny bubbles in the solution cannot be completely removed, and after subsequent coating and drying to form a film, the tiny bubbles will form cavities, thereby providing channels for the contact between the solvent molecules and the current collector. Therefore, the vacuum degree is controlled to be 900~960 kPa, such as 920 kPa, 930 kPa, 950 kPa; preferably 900~940 kPa, (one standard atmospheric pressure is 1 MPa, 1 MPa=1000kPa).
[0065] Specifically, in the above step 4, it is considered that if the vacuum degassing treatment time is too long, the solution may boil and the solvent may evaporate too quickly; if the vacuum degassing treatment time is too short, it may be difficult to discharge the tiny bubbles in the solution. Therefore, the vacuum degassing treatment time is controlled to be 2 to 15 minutes, such as 5 minutes, 7 minutes, 10 minutes, or 12 minutes; preferably 3 to 12 minutes.
[0066] Specifically, in the above step 5, the current collector can be one or more of Al foil, Cu foil, Zn foil, Mg foil, stainless steel foil, stainless steel mesh, Ni mesh, Ti foil, Ti mesh, carbon paper, carbon cloth and graphite paper.
[0067] Specifically, in the above step 5, the current collector can be designed into various shapes and sizes according to actual needs.
[0068] Specifically, in the above step 5, the current collector can be pre-cut by a cutting machine to cut the tab portion according to actual needs.
[0069] Specifically, in the above step 5, the tab cutting work is completed by unwinding the current collector at the front end, cutting it with a cutting machine, and rewinding it at the rear end.
[0070] Specifically, in the above step 5, both the upper and lower surfaces of the lower end of the tab need to be coated, and the side surfaces of the tab coated with the adhesive coating need to be sealed with the adhesive layer.
[0071] Specifically, in the above step 5, a spray gun may be used to seal the side of the pole ear with a glue layer. The spray gun solution spray rate is controlled to be 1-5 μL / mm². For example, 2 μL / mm², 3 μL / mm², 4 μL / mm².
[0072] Specifically, in the above step 5, coating can be applied to one side first and then to the other side; specifically comprising the following steps:
[0073] Step 5: Flatten the current collector and evenly coat the solution C on the lower side of the current collector tab;
[0074] Step 6, pre-drying the current collector;
[0075] Step 7, turn over the pre-dried current collector, repeat step 5, and ensure that the coated front and back positions overlap;
[0076] Step 8: Repeat the pre-drying operation in step 6, and then increase the temperature for drying;
[0077] Step 9: seal the side of the current collector pole ear with a glue layer and dry it, wherein the sealed portion of the side of the coated current collector pole ear is the side of the pole ear coated with the coating, to obtain a coated current collector.
[0078] Specifically, in the above step 5, the current collector can be spread on a flat and clean glass plate, and solution C can be evenly coated on 30% to 80% of the lower surface of the current collector tab, for example, 40%, 50%, 60%, 70%; preferably 50% to 70%.
[0079] Specifically, in the above step 6, if the pre-drying temperature is too high, it is easy to cause the solution to form a film too quickly, and the internal stress cannot be released in time, causing the ear of the current collector to deform; if the pre-drying temperature is too low, the solution will not be completely dried. When the back is subsequently coated, the solution on the front will adhere to the glass plate, causing coating damage. If the pre-drying time is too long, the production efficiency will be low; if the pre-drying time is too short, the solution cannot be well filmed. Therefore, the pre-drying temperature is controlled to be 30~90℃, for example, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃; preferably 35~70℃; the pre-drying time is 0.5~5 min, for example, 1 min, 2 min, 3 min, 4 min; preferably 0.5~3 min.
[0080] Specifically, in the above step 8, if the drying temperature is too high, it is easy to cause oxidation of the current collector, too fast evaporation of the solvent, and uneven coating. If the drying temperature is too low, the coating cannot be completely dried. If the drying time is too long, it is easy to cause the coating glue on the surface of the coating to self-solidify, making it difficult for the internal solvent to evaporate and the coating to dry. If the drying time is too short, it is easy to cause incomplete drying of the solution or poor film formation of the coating. Therefore, the drying temperature is controlled to be higher than the pre-drying temperature, for example, the drying temperature is 60~200℃, for example, 70℃, 80℃, 90℃, 100℃, 120℃, 150℃, 170℃, 180℃, 190℃; preferably 60~150℃; the drying time is 2~10 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min; preferably 3~8 min.
[0081] Specifically, in the above step 9, the solution C in step 5 is used to seal the side of the current collector tab with a glue layer.
[0082] Specifically, in the above step 9, a spray gun can be used to seal the side of the current collector tab with a glue layer. Considering that the spray speed of the spray gun is too high, the impact force of the solution is too large, causing damage to the current collector; if the spray speed is too low, it is easy to cause the solution to fall in a parabolic curve, so that the sprayed solution cannot be accurately sprayed to the tab position. If the spraying time is too long, it is easy to cause the solution to be affected by gravity after the side coating, and the film thickness is uneven; if the spraying time is too short, it cannot be guaranteed that the side is completely covered by the coating, and there is a risk of current collector leakage. Therefore, the solution spray rate of the spray gun is controlled to be 1~5μL / mm². For example, 2 μL / mm², 3 μL / mm², 4 μL / mm².
[0083] Specifically, in the above step 5, the coating can be performed on both sides simultaneously by a coating machine; specifically comprising the following steps:
[0084] S501, evenly coating solution C on both sides of the lower end of the current collector tab;
[0085] S502, drying the current collector;
[0086] S503, sealing the side of the current collector electrode tab with a glue layer and drying the side, wherein the sealed portion of the side of the coated current collector electrode tab is the electrode tab side coated with the coating, to obtain a coated current collector.
[0087] Specifically, in the above S502, if the drying temperature is too high, it is easy to cause oxidation of the current collector, too fast evaporation of the solvent, and uneven coating. If the drying temperature is too low, the coating cannot be completely dried. If the drying time is too long, it is easy to cause the coating glue on the surface of the coating to self-solidify, making it difficult for the internal solvent to evaporate and the coating to dry. If the drying time is too short, it is easy to cause incomplete drying of the solution or poor film formation of the coating. Therefore, the drying temperature is controlled to be 60~200℃, for example, 70℃, 80℃, 90℃, 100℃, 120℃, 150℃, 170℃, 180℃, 190℃; preferably 60~150℃.
[0088] Specifically, in the above S503, a spray gun can be used to seal the side of the current collector with a glue layer. Considering that the spray speed of the spray gun is too high, the impact force of the solution is too large, causing damage to the current collector; if the spray speed is too low, it is easy to cause the solution to fall in a parabolic curve, so that the sprayed solution cannot be accurately sprayed to the position of the pole ear. If the spraying time is too long, it is easy to cause the solution to be affected by gravity after the side coating, and the film thickness is uneven; if the spraying time is too short, it cannot be guaranteed that the side is completely covered by the coating, and there is a risk of leakage of the current collector. Therefore, the solution spray speed of the spray gun is controlled to be 1~5μL / mm². For example, 2 μL / mm², 3 μL / mm², 4 μL / mm².
[0089] It should be noted that in the above preparation method, the coating adhesive can combine with water molecules and organic solvent molecules by intermolecular forces in the microscopic form; by first adding the dispersant, the coating adhesive can be effectively dispersed so that it is evenly distributed in solution B, and then the anti-shrinkage agent is added. In the subsequent drying process, the tension of solution C can be guaranteed to be equal everywhere, so that the coating adhesive can form a more uniform film.
[0090] The present invention also provides an aqueous battery, which comprises the above-mentioned coating current collector.
[0091] Specifically, the aqueous battery can be a new type of aqueous secondary battery such as an aqueous lithium-ion battery, an aqueous sodium-ion battery, an aqueous zinc-ion battery, an aqueous aluminum-ion battery, a zinc-nickel secondary battery, a supercapacitor, an aqueous nickel-bismuth battery, and an aqueous zinc-air battery.
[0092] The electrode tab of the coated current collector of the present invention is provided with a glue coating, which has insulating properties and can block direct contact between the electrolyte and the current collector inside the coating, avoiding electron exchange between the conductive particles in the electrolyte and the current collector, thereby inhibiting corrosion of the current collector.
[0093] The electrode tab of the coated current collector of the present invention is provided with a glue coating, and the conduction of electrons occurs inside the current collector, which will not increase the ohmic resistance of the current collector part in the battery and has no inhibitory effect on the cycle performance of the battery.
[0094] In the preparation method of the coated current collector of the present invention, the glue solution is subjected to vacuum degassing treatment to prevent air from being mixed into the glue solution during the preparation process, and to prevent air from causing incomplete subsequent drying and film formation of the glue solution when the electrode ear of the current collector is coated, and the current collector is exposed and corroded by salt creep.
[0095] In the preparation method of the coated current collector of the present invention, by adding an appropriate amount of dispersant, the glue liquid can be effectively and evenly dispersed, and a coating with uniform thickness and density can be prepared when preparing the coated current collector, and it can be firmly attached to the surface of the collector's pole ear, effectively enhancing the tensile strength at the collector's pole ear, making it less likely to break; by adding a trace amount of anti-shrinkage agent, the glue liquid can be effectively prevented from excessively shrinking during the pre-drying and drying process of the current collector, causing deformation and damage to the current collector.
[0096] The current collector prepared by the present invention is a new type of coating current collector with conductive middle layer and insulating outer layer. Compared with the traditional current collector, it has higher tensile strength, can effectively inhibit the salt climbing phenomenon of electrolyte, alleviate the corrosion of the current collector, and extend the cycle life of the aqueous battery; for example, the tensile strength of the pole ear of the coating current collector of the present invention can reach more than 6.5N, such as 6.58~14N, which is more than 1.3 times the tensile strength of the traditional current collector without glue coating, such as 1.3~2.5 times. The coating current collector of the present invention is suitable for aqueous batteries with electrolytes of different components and has strong adaptability.
[0097] The aqueous battery of the present invention has a long cycle life, for example, the cycle life of the aqueous battery of the present invention reaches more than 200 cycles, which is more than twice, for example, 2 to 6 times, of the conventional battery without a gel-coated current collector. The capacity retention rate of the aqueous battery is above 88%, for example, 88.84% to 92%.
[0098] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0099] Embodiment 1
[0100] This embodiment provides a coating current collector, such as Figure 1 As shown, the coated current collector includes a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is provided on the surface of the pole ear. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.
[0101] The method for preparing the coating current collector of this embodiment comprises the following steps:
[0102] 1. Take 2 mL of deionized water and 10 mL of DMF and place them in a container. Add a magnetic stirrer at a speed of 180 r / min to obtain solution A.
[0103] 2. Weigh 3 g of ABS plastic glue and add it to solution A, stir and dilute until mixed evenly to obtain solution B;
[0104] 3. Weigh 0.15 g of sodium tripolyphosphate as a dispersant and 0.006 g of polypropylene oxide as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve them to obtain solution C.
[0105] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 920 kPa for 6 min;
[0106] 5. According to the requirements of aqueous sodium-ion batteries, select Al foil as the current collector and cut it into a suitable shape and size;
[0107] 6. Place the Al foil current collector on a flat and clean glass plate, and use a pipette to evenly apply 100 μL of solution C on 70% of the surface of the lower end of the current collector tab;
[0108] 7. Pre-dry the Al foil current collector at 50 °C for 2 min;
[0109] 8. Turn over the pre-dried Al foil current collector and repeat step 6, making sure that the front and back sides of the glue coating overlap;
[0110] 9. Repeat the pre-drying operation of step 7 for the Al foil current collector, then raise the temperature to 100 °C and keep it at this temperature for 6 min for drying;
[0111] 10. Overlap multiple Al foil current collectors, spray solution C at a rate of 3 μL / mm² through a spray gun, seal the sides of the coated current collector with a glue layer, and dry them at 100 °C for 6 min. The sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain the coated Al foil current collector. The thickness of the glue coating in this embodiment is 20 μm.
[0112] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Al foil current collector. According to the selected coated Al foil current collector, the electrode sheet of the aqueous sodium ion battery is prepared, the diaphragm is cut, the electrolyte is prepared, etc., wherein lithium manganese oxide is used as the positive electrode, sodium titanium phosphate is used as the negative electrode, and the non-woven fabric is used as the diaphragm. An appropriate amount of 2M CH 3 COOLi+1M CH 3 COONa solution was used as the electrolyte, and the aqueous sodium-ion battery was assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical properties of the aqueous sodium-ion battery were characterized.
[0113] Comparative Example 1:
[0114] Except that the Al foil current collector is not treated in any way, the assembly and testing methods of the other aqueous sodium ion batteries are the same as those in Example 1.
[0115] Embodiment 2
[0116] This embodiment provides a coated current collector, which includes a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating, and the raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.
[0117] The method for preparing the coating current collector of this embodiment comprises the following steps:
[0118] 1. Take 3 mL of deionized water and 12 mL of DMF and place them in a container. Add a magnetic stirrer at a speed of 120 r / min to obtain solution A.
[0119] 2. Weigh 2.5 g of polyvinyl acetate emulsion and add it to solution A, stir and dilute until mixed evenly to obtain solution B;
[0120] 3. Weigh 0.075 g of sodium dodecyl sulfate as a dispersant and 0.0125 g of monoglyceride as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve them to obtain solution C.
[0121] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 910 kPa for 10 min;
[0122] 5. According to the requirements of aqueous zinc-ion batteries, select Zn foil as the current collector and cut it into appropriate shape and size;
[0123] 6. Place the Zn foil current collector on a flat and clean glass plate, and use a pipette to evenly apply 80 μL of solution C on 60% of the surface of the lower end of the current collector tab;
[0124] 7. Pre-dry the Zn foil current collector at 60 °C for 1 min;
[0125] 8. Turn over the pre-dried Zn foil current collector and repeat step 6, making sure that the front and back sides of the glue coating overlap;
[0126] 9. Repeat the pre-drying operation of step 7 for the Zn foil current collector, then raise the temperature to 140 °C and keep it at this temperature for 4 min for drying;
[0127] 10. Overlap multiple Zn foil current collectors, spray solution C at a rate of 5 μL / mm² through a spray gun to seal the sides of the coated current collectors with glue, and dry them at 140°C for 4 min, where the sealed side of the coated current collector is the side of the coated pole ear, and finally obtain a coated Zn foil current collector. The thickness of the glue coating in this embodiment is 40 μm.
[0128] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Zn foil current collector. According to the selected prepared coated Zn foil current collector, the electrode sheet preparation, diaphragm cutting, electrolyte preparation and other operations of the aqueous zinc ion battery are carried out, wherein MnO 2 As the positive electrode, Zn powder as the negative electrode, glass fiber as the separator, and inject an appropriate amount of 1.5M ZnSO 4 The solution is used as an electrolyte, and the aqueous zinc ion battery is assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical performance of the aqueous zinc ion battery is characterized.
[0129] Comparative Example 2:
[0130] Except that the Zn foil current collector is not treated in any way, the rest of the assembly and testing methods of the aqueous zinc ion battery are the same as those of Example 2.
[0131] Embodiment three:
[0132] This embodiment provides a coated current collector, which includes a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating, and the raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.
[0133] The method for preparing the coating current collector of this embodiment comprises the following steps:
[0134] 1. Take 1 mL of deionized water, 5 mL of DMF and 5 mL of hydroxypyridine and place them in a container. Add a magnetic stirrer and stir at a speed of 240 r / min to obtain solution A.
[0135] 2. Weigh 1.5 g of polyvinyl chloride and add it to solution A, stir and dilute until the mixture is evenly mixed to obtain solution B;
[0136] 3. Weigh 0.03 g of water glass and 0.06 g of sodium pyrophosphate as dispersants and 0.0135 g of inorganic medium ethylene glycol as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve them to obtain solution C.
[0137] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 930 kPa for 12 min;
[0138] 5. According to the requirements of aqueous aluminum ion batteries, select Ni foil as the current collector and cut it into a suitable shape and size;
[0139] 6. Evenly apply solution C on 50% of the double-sided surface of the lower end of the current collector tab;
[0140] 7. Dry the Ni foil current collector at 120°C for 8 min to obtain a coated Ni foil current collector;
[0141] 8. Overlap multiple Ni foil current collectors, spray solution C at a rate of 2 μL / mm² through a spray gun to seal the sides of the coated current collectors with glue, and dry them at 120 °C for 8 min, where the sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain the coated Ni foil current collector. The thickness of the glue coating in this embodiment is 50 μm.
[0142] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Ni foil current collector. According to the selected coated Ni foil current collector, the electrode sheet preparation, diaphragm cutting, electrolyte preparation and other operations of the aqueous aluminum ion battery are carried out, wherein LiV 3 O 8 As the positive electrode, Al / CNTs as the negative electrode, cellulose as the separator, and injected with an appropriate amount of 3M Al(OTF) 3 The solution is used as an electrolyte, and the N / P ratio of the positive and negative electrodes is controlled to assemble aqueous aluminum ion batteries, and the electrochemical performance of aqueous sodium ion batteries is characterized.
[0143] Comparative Example 3:
[0144] Except that the Ni foil current collector is not treated in any way, the rest of the assembly and testing methods of the aqueous aluminum ion battery are the same as those of Example 3.
[0145] Embodiment 4:
[0146] This embodiment provides a coated current collector, which includes a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating, and the raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.
[0147] The method for preparing the coating current collector of this embodiment comprises the following steps:
[0148] 1. Take 2 mL of deionized water, 2 mL of isopropanol and 6 mL of acetonitrile and place them in a container. Add a magnetic stirrer at a speed of 150 r / min to obtain solution A.
[0149] 2. Weigh 2 g of epoxy resin and 3 g of VAE emulsion, add them to solution A, stir and dilute until mixed evenly, to obtain solution B;
[0150] 3. Weigh 0.2 g of fatty acid polyethylene glycol ester as a dispersant and 0.035 g of methyl glycerol as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve them to obtain solution C.
[0151] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 940 kPa for 3 min;
[0152] 5. Select graphite paper as the current collector and cut it into the appropriate shape and size;
[0153] 6. Place the graphite paper current collector on a flat and clean glass plate, and use a pipette to evenly apply 50 μL of solution C on 65% of the surface of the lower end of the current collector tab;
[0154] 7. Pre-dry the graphite paper current collector at 40 °C for 1 min;
[0155] 8. Turn over the pre-dried graphite paper current collector, repeat step 6, and ensure that the front and back sides of the glue coating overlap;
[0156] 9. Repeat the pre-drying operation of step 7 for the graphite paper current collector, then raise the temperature to 80° C. and keep it warm for 5 minutes to dry it, to obtain a coated graphite paper current collector;
[0157] 10. Overlap multiple sheets of graphite paper current collectors, spray solution C at a rate of 1 μL / mm² through a spray gun, so as to seal the sides of the coated current collector with a glue layer, and dry them at 80°C for 5 min, wherein the sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain a coated graphite paper current collector. The thickness of the glue coating in this embodiment is 30 μm.
[0158] This embodiment also provides an aqueous battery, which includes the above-mentioned coated graphite paper current collector. According to the selected coated graphite paper current collector, the electrode sheet of the supercapacitor is prepared, the diaphragm is cut, the electrolyte is prepared, etc., wherein NiCo LDH is used as the positive electrode, AC is used as the negative electrode, and glass fiber is used as the diaphragm. An appropriate amount of 6M KOH solution is injected as the electrolyte, and the supercapacitor is assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical performance of the supercapacitor is characterized.
[0159] Comparative Example 4:
[0160] Except that the graphite paper current collector is not treated in any way, the rest of the supercapacitor assembly and testing methods are the same as those in Example 4.
[0161] The tensile strength of the current collector tabs of the embodiments and comparative examples are shown in Table 1 below. It can be seen that the current collector tabs of the present invention have high tensile strength, the current collector of the present invention has no obvious salt creep after the battery of the present invention is cycled, and the cycle life of the battery of the present invention is long.
[0162] Table 1 Current collector tab tensile strength and battery performance of the embodiments and comparative examples
[0163]
[0164] Figure 2 1 is a comparison diagram of the current collectors of Example 1 of the present invention and Comparative Example 1. The left side is the coating current collector of Example 1, and the right side is the current collector of Comparative Example 1.
[0165] Figure 3 3 is a comparison chart of the tensile strength of the current collector tabs of Example 1 of the present invention and Comparative Example 1. It can be seen that the tensile strength of the current collector tabs of Example 1 is higher than that of Comparative Example 1.
[0166] Figure 4 1 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 1 of the present invention and Comparative Example 1; the left side is Example 1 and the right side is Comparative Example 1; it can be seen that there is no obvious salt creep in Example 1.
[0167] Figure 5 It is a cycle performance diagram of the aqueous sodium ion battery assembled in Example 1 of the present invention and Comparative Example 1.
[0168] Figure 6 1 is a comparison diagram of the current collectors of Example 2 and Comparative Example 2 of the present invention, wherein the left side is the coated current collector of Example 2, and the right side is the current collector of Comparative Example 2.
[0169] Figure 7 3 is a comparison chart of the tensile strength of the current collector tabs of Example 2 of the present invention and Comparative Example 2. It can be seen that the tensile strength of the current collector tabs of Example 2 is higher than that of Comparative Example 2.
[0170] Figure 8 1 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 2 of the present invention and Comparative Example 2; the left side is Example 2, and the right side is Comparative Example 2; it can be seen that there is no obvious salt creep in Example 2.
[0171] Fig. 9 It is a cycle performance diagram of the aqueous zinc ion battery assembled by Example 2 of the present invention and Comparative Example 2.
[0172] The inventors have conducted a large number of experimental studies during the research process, and now list some solutions with poor performance as comparative examples as follows.
[0173] Comparative Example 5
[0174] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that, in step 2, 15 g of polyvinyl acetate emulsion is weighed.
[0175] Comparative Example 6
[0176] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that in step 3, 0.9 g of sodium dodecyl sulfate is weighed as a dispersant.
[0177] Comparative Example 7
[0178] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that in step 3, 0.5 g of monoglyceride is weighed as an anti-shrinkage agent.
[0179] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A water-based battery coating current collector, characterized in that: The coated current collector comprises a current collector substrate and a pole ear arranged on the current collector substrate, a rubber coating is arranged on the surface of the pole ear, and the raw materials for preparing the rubber coating are water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent; the mass of the dispersant is 2% to 10% of the mass of the coating glue, and the mass of the anti-shrinkage agent is 0.05% to 2% of the mass of the coating glue; the volume ratio of the water to the organic solvent is 0.01 to 1:1; The coating adhesive is one or more of ABS plastic adhesive, polyacrylic resin, epoxy resin, polyvinyl chloride, organic silicone adhesive, polyvinyl acetate emulsion and VAE emulsion; The dispersant is one or more of water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester and cellulose derivatives; The anti-shrinkage agent is one or more of polypropylene oxide, inorganic vehicle ethylene glycol and monoglyceride.
2. The coating current collector according to claim 1, characterized in that: The rubber coating is provided on 30% to 80% of the surface of the lower end of the tab.
3. The coating current collector according to claim 1, characterized in that: The adhesive coating is obtained by coating with adhesive liquid. The coating adhesive is added into a mixed solution of water and an organic solvent, and then a dispersant and an anti-shrinkage agent are added in sequence to obtain the adhesive liquid.
4. A method for preparing a coating current collector, characterized in that: The preparation method is used to prepare the coating current collector according to any one of claims 1 to 3, comprising the following steps: Step 1, mixing water and an organic solvent to obtain a solution A; Step 2, adding the coating glue to solution A and mixing to obtain solution B; Step 3, adding the dispersant and the anti-shrinkage agent to the solution B in sequence and mixing them to obtain a solution C; Step 4, subjecting solution C to vacuum degassing treatment; Step 5: coating solution C on the lower surface of the tab; and then drying to obtain a coated current collector.
5. The preparation method according to claim 4, characterized in that: In step 2, the volume ratio of the coating glue mass to the solution A is 1 g: 1-10 mL.
6. The preparation method according to claim 4, characterized in that: In step 3, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating glue.
7. The preparation method according to claim 4, characterized in that: In step 3, the mass of the anti-shrinkage agent is controlled to be 0.05% to 2% of the mass of the coating adhesive.
8. The preparation method according to claim 4, characterized in that: In the step 1, the stirring speed is 50-300 r / min.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step 5, the drying temperature is 60-200°C.
10. An aqueous battery, characterized in that: The aqueous battery comprises the coating current collector according to any one of claims 1 to 3 or the coating current collector prepared by the preparation method according to any one of claims 4 to 9.
Citation Information
Patent Citations
High-safety and high-energy density lithium ion battery
CN107768589A
A positive electrode sheet for improving safety performance of a battery and a method thereof
CN108987669A
High-voltage-resistant tab protection adhesive tape for semi-solid-state battery and preparation method of high-voltage-resistant tab protection adhesive tape
CN117801710A
Battery water-based negative electrode slurry and preparation method thereof
CN118156426A